Examples of Spiritual Enlightenment and Moral Education in the Hadiths. - PhD. Samiev Asroridin Sayfidinovich. (Peerian Journals Publishing, 2022)
The article discusses the negative changes that have taken place in the behavior of students as a result of the integration of religions, national values, traditions, languages and cultures under the influence of globalization due to the high level of development of science and technology. The use of the Qur'an and the exemplary life and hadiths of the Prophet Muhammad (peace and blessings of Allah be upon him) in the educational process is one of the most pressing problems of our time, and recommendations are given for its solution
Keywords: Qur’an; Prophet; Hadith; spirituality